2009
DOI: 10.2471/blt.08.055715
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol to prevent and treat postpartum haemorrhage: a systematic review and meta-analysis of maternal deaths and dose-related effects

Abstract: Objective To review maternal deaths and the dose-related effects of misoprostol on blood loss and pyrexia in randomized trials of misoprostol use for the prevention or treatment of postpartum haemorrhage. Methods We searched the Cochrane Controlled Trials Register and Pubmed, without language restrictions, for "(misoprostol AND postpartum) OR (misoprostol AND haemorrhage) OR (misoprostol AND hemorrhage)", and we evaluated reports identified through the Cochrane Pregnancy and Childbirth Group search strategy. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 61 publications
5
80
1
Order By: Relevance
“…As the side effects are dose related, a dose of 400 mcg was chosen in the present study to minimize maternal adverse effects with optimal therapeutic benefit. In a recent review, 400 mcg of misoprostol was found to be safer than 600 mcg and just as effective [11].…”
Section: Discussionmentioning
confidence: 99%
“…As the side effects are dose related, a dose of 400 mcg was chosen in the present study to minimize maternal adverse effects with optimal therapeutic benefit. In a recent review, 400 mcg of misoprostol was found to be safer than 600 mcg and just as effective [11].…”
Section: Discussionmentioning
confidence: 99%
“…The database search revealed two systematic reviews 10,16 and further studies were also identified from the sources. Studies were excluded if duplicate, considering injectable prostaglandins, non-RCTs, not reported in English, in high-income and hospital settings.…”
Section: Methodsmentioning
confidence: 99%
“…Hofmeyr et al presented no more efficacy for higher dose of misoprostol in preventing hemorrhage more than 1,000 cc through a meta-analysis [24]. However, synergistic effects of two agents would allow a reduction in dose for both agents and therefore limit the side effects while improving efficacy.…”
Section: Discussionmentioning
confidence: 99%